The feasibility and utility of optical coherence tomography directed histopathology for surgical margin assessment of canine mast cell tumours. (1st October 2020) - Dornbusch, Josephine A.; Cocca, Christina; Jennings, Ryan; Samuelson, Jonathan; Vieson, Miranda; Huang, Pin‐Chieh; Boppart, Stephen A.; Wavreille, Vincent A.; Selmic, Laura E.
Abstract: Histopathologic surgical margin assessment in veterinary patients is an imprecise science with assessment limited to a small proportion of the surgical margin due to time and finances. Incomplete excision of canine mast cell tumours (MCTs) alters treatment recommendations and prognosis. Optical coherence tomography (OCT) is a novel imaging modality that has been reported in a single veterinary study for surgical margin assessment. Twenty‐five dogs with 34 MCTs were enrolled in a prospective pilot‐study to assess the imaging characteristics of canine MCTs with OCT and to evaluate the feasibility and utility of OCT‐guided histopathology. All dogs underwent routine surgical excision of MCTs. OCT imaging was used to assess the entire surgical margin prior to placement in formalin. Either normal areas or areas suspected of incomplete MCT excision were inked. Standard histopathologic sectioning and tangential sectioning of inked areas were performed and compared to OCT results. OCT identified MCT near the surgical margin in 10 of 26 specimens (38.4%). Four specimens suspicious for incomplete margins on OCT had incomplete MCT excision that was missed on standard histopathologic sectioning. Six specimens had OCT‐guided sections taken as suspicious, which did not show MCT on histopathology. OCT‐guided pathology sections were able to detect incompletely excised MCT near the surgical margin with a sensitivity of 90% and specificity of 56.2% in this preliminary study. OCT imaging shows promise for guiding pathologists to areas of interest to improve the diagnostic accuracy of surgical margin assessment in excised canine MCTs.